2018
DOI: 10.1002/phar.2174
|View full text |Cite
|
Sign up to set email alerts
|

Tenofovir Alafenamide for the Treatment of Chronic Hepatitis B Monoinfection

Abstract: Tenofovir alafenamide (TAF) is indicated for adult patients with chronic hepatitis B virus (HBV) infection with compensated liver disease at an oral dose of 25 mg/day. TAF is a more stable prodrug in the plasma than tenofovir disoproxil fumarate (TDF), leading to decreased plasma exposure of tenofovir. Decreased exposure is thought to reduce the risk of long-term TDF toxicities, such as nephrotoxicity and decreased bone mineral density (BMD). TAF, a nucleotide reverse transcriptase inhibitor, has the same mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…Tenofovir alafenamide fumarate (known as TAF) [6][7][8] is a novel prodrug derivative of the well-known nucleotide reverse transcriptase inhibitor (NtRTI) tenofovir (TFV) [9][10][11], which was initially developed for the treatment of HIV infection as tenofovir disoproxil fumarate (TDF) in the late 1990s [12][13][14] and marketed under the tradename Viread ® since 2001 [15]. TAF, as a new type of TFV prodrug, was approved as a mono therapy (Vemlidy ® ) in November 2016 for the treatment of chronic hepatitis B virus infection [16][17][18][19][20] in adults with compensated liver disease by the U.S Food & Drug Administration (FDA). Interestingly, therapy (Vemlidy ® ) in November 2016 for the treatment of chronic hepatitis B virus infection [16][17][18][19][20] in adults with compensated liver disease by the U.S Food & Drug Administration (FDA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tenofovir alafenamide fumarate (known as TAF) [6][7][8] is a novel prodrug derivative of the well-known nucleotide reverse transcriptase inhibitor (NtRTI) tenofovir (TFV) [9][10][11], which was initially developed for the treatment of HIV infection as tenofovir disoproxil fumarate (TDF) in the late 1990s [12][13][14] and marketed under the tradename Viread ® since 2001 [15]. TAF, as a new type of TFV prodrug, was approved as a mono therapy (Vemlidy ® ) in November 2016 for the treatment of chronic hepatitis B virus infection [16][17][18][19][20] in adults with compensated liver disease by the U.S Food & Drug Administration (FDA). Interestingly, therapy (Vemlidy ® ) in November 2016 for the treatment of chronic hepatitis B virus infection [16][17][18][19][20] in adults with compensated liver disease by the U.S Food & Drug Administration (FDA).…”
Section: Introductionmentioning
confidence: 99%
“…TAF, as a new type of TFV prodrug, was approved as a mono therapy (Vemlidy ® ) in November 2016 for the treatment of chronic hepatitis B virus infection [16][17][18][19][20] in adults with compensated liver disease by the U.S Food & Drug Administration (FDA). Interestingly, therapy (Vemlidy ® ) in November 2016 for the treatment of chronic hepatitis B virus infection [16][17][18][19][20] in adults with compensated liver disease by the U.S Food & Drug Administration (FDA). Interestingly, according to the FDA data, TAF is marketed as a hemifumarate [21].…”
Section: Introductionmentioning
confidence: 99%
“…The most influential recommendations for patients are lifestyle and diet. Other studies have found that most patients in China find themselves in the middle and late stages of the disease when they are suffering from hepatitis B [34]and have symptoms such as nausea and fatigue [35]. Influenced by the environment and other factors [36], they are likely to develop into liver cancer and reduce their quality of life [37].…”
Section: Discussionmentioning
confidence: 99%
“…The prodrug tenofovir alafenamide (TAF) is 10 times more potent than tenofovir disoproxil fumarate (TDF), and has the added advantage that it is taken up into cells from the plasma as the prodrug, which is converted to the parent drug and then to the active intracellular diphosphate inside the cell [9]. In addition, from the perspective of prevention, TAF has activity against both hepatitis B virus (HBV) and HIV, and could potentially prevent both infections, in addition to treating them in those who have already acquired coinfection [10].…”
Section: Tenofovir Prodrugsmentioning
confidence: 99%